Good night, Lala - Calica, Corazon Ordonez; Calica, Maya O.; Montenejo, Jinggo (Quezon City Adarna House, 2013)
"Here are eight wonderful stories of Corazon Ordonez-Calica. Set against the backdrop of wartime Pampanga are tales of enchanted stones, cathing frogs, and dodging bullets!"
Corazon the storyteller -- The duwende -- Victoria's secret -- My mother, Ima -- Bata, betute -- Escape to Pangatlan -- An enchanted garden -- Pruding and the caimito trees -- Bang-bang in Pangatlan.
Keywords: Tales -- Philippines -- Pampanga